2020
DOI: 10.7151/dmgt.2145
|View full text |Cite
|
Sign up to set email alerts
|

Neighbor sum distinguishing total choosability of IC-planar graphs

Abstract: Two distinct crossings are independent if the end-vertices of the crossed pair of edges are mutually different. If a graph G has a drawing in the plane such that every two crossings are independent, then we call G a plane graph with independent crossings or IC-planar graph for short. A proper total-kcoloring of a graph G is a mapping c : V (G) ∪ E(G) → {1, 2,. .. , k} such that any two adjacent elements in V (G) ∪ E(G) receive different colors. Let

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Wang et al [11] confirmed Conjecture 2 for every planar graph G with maximum degree ∆(G) ≥ 8 but without theta graphs Θ 2,1,2 . Song et al [12] discussed the NSD total L-coloring of any IC-planar graph and obtained the following theorem.…”
Section: Conjecture 1 ([2]mentioning
confidence: 99%
“…Wang et al [11] confirmed Conjecture 2 for every planar graph G with maximum degree ∆(G) ≥ 8 but without theta graphs Θ 2,1,2 . Song et al [12] discussed the NSD total L-coloring of any IC-planar graph and obtained the following theorem.…”
Section: Conjecture 1 ([2]mentioning
confidence: 99%